Revisiting the Indonesian Criminal Procedure Code: Paradigmatic Issues and the Challenges of an Evolving Era - Wisnubroto, Aloysius (UIN Sunan Kalijaga Yogyakarta, 2024)
The reform of criminal procedure law in Indonesia has become a necessity, as the Criminal Procedure Code (KUHAP), after more than four decades of implementation, is confronted with the transformations of human civilization that characterize the postmodern era. This study seeks to address two key questions: why the postmodern condition necessitates a response in the renewal of Indonesian criminal procedure law, and how the KUHAP should be reconceptualized. Employing a juridical-normative approach, this research argues that reform cannot be limited to technical procedural adjustments but must extend to a paradigmatic shift. Rooted in modern legal concepts shaped by positivism, the KUHAP must adapt to the challenges of postmodern realities, which are increasingly complex, non-linear, global, segmentary, and multiversal. To bridge this gap, a progressive concept of criminal procedure law is required—one that maintains the principles of lex scripta, lex certa, and lex stricta, while simultaneously allowing space for rationally and morally justifiable legal breakthroughs in extraordinary circumstances.